Two new Peruvian species of Brayopsis (Brassicaceae; Cruciferae), and a key to the species - Al-Shehbaz, Ihsan A.; Cano, Asunción; Trinidad, Huber; Gonzáles, Paúl; Huamán, Elluz (Phytotaxa, 2018)
Two new Peruvian species of Brayopsis, B. limensis and B. cuscoensis, are described an illustrated, and their relationships and distinguishing characters from their nearest relatives are discussed. A key to the nine species of Brayopsis is presented.